Adapting to change: working with digital sound using open source software in a teaching and learning environment. Issue 2 (26th November 2008) - Moore, Adrian; Moore, Dave
This article contributes towards knowledge and understanding of the creative use of software and hardware tools for computer music. It stems from a need to reassess strategic spending within an academic department on music IT, and an interest in the advantages of open source software for managing musical and collaborative projects. The authors discuss the most practical way of assessing the use of Linux, a completely open source software platform with the aim of understanding how compositional paradigms migrate between computer operating systems, noting similarities between systems, and highlighting strengths and weaknesses of the process.It is apparent that the Linux platform has much to offer, but remains limited in a number of areas of music IT that are used extensively in academia, industry and at home. However, as a platform for teaching and learning computer music it is an ideal tool, though we conclude that some introduction at the outset is required for those who are uninitiated to a Linux-based system. The teaching and learning initiative expected students, by the end of a three-year undergraduate degree programme, to be creating their own tools and to have a good understanding of related operating systems.